Impact of Computer-Based Peer Review on College Students’ Performance and Perceived Self-Efficacy in an Online Graphic Design Course - Sharon P. Wagner; Tracy Rutherford (Journal of Applied Communications, 2019)
Prior research has indicated that the incorporation of computer-based peer review into writing instruction increases student engagement, improves student performance, and increases student perceptions of self-efficacy. This study used a quasi-experimental untreated control group design to examine the impact of computer-based peer review on student performance and perceived self-efficacy in an undergraduate agricultural graphic design course. The impact of participation in computer-based peer review on performance scores was investigated using a MANOVA. After two rounds of peer review, students improved their overall course performance by one-half letter grade. Perceptions of self-efficacy were further analyzed using a one-way repeated measures ANOVA. Most (54.17%) students who participated in the computer-based peer review process reported increases in perceived self-efficacy in graphic design. The findings from this study indicate the benefits of computer-based peer review extend to instruction in graphic design courses.
Keywords: peer review; self-efficacy; graphic design; teaching strategy; distance learning